Editorial commentary:Aspirin resistance: more emphasis on definition and appropriate use of platelet function tests is needed - Gasparyan, Armen Y. (Archives of Medical Science, 2009)
Commentary on The influence of aspirin resistance on non-fatal coronary events following percutaneous coronary interventions